PENGEMBANGAN MODEL PENGAMBILAN KEPUTUSAN MENGGUNAKAN FUZZY MULTIPLE ATTRIBUTE DECISION MAKING UNTUK IDENTIFIKASI POTENSI KEMISKINAN DI KABUPATEN PRINGSEWU - Jimi Ali Baba; Sudewi Sudewi; Erma Dwiyani (LPPM STMIK Pringsewu, 2019)
Poverty is a difficult problem to deal with. According to the current BPS poverty rate in Indonesia it still reaches 11.7% with the poverty depth index increasing from 1.75% (March 2013) to 1.89%. Then the poverty severity index increased from 0.43% (March) to 0.48%. The poverty line during the period from March to September 2013 increased by 7.85%. For this reason, criteria are needed to determine whether a family is classified as poor or not in Pringsewu District does not yet have criteria with a level of importance to make these decisions. For this reason, a decision support system is needed that can be an alternative decision support in determining poverty potential in Pringsewu district. In the calculation to determine the level of family poverty the Fuzzy Multiple Attribute Decision Making method is used. The manual test results using eight criteria from Nine alternatives where Alternative 6 is the alternative with the highest value of 75.25, and the lowest alternative is in Alternative 4, so Alternative 4 is an alternative identified as potential poverty in the Pringsewu District with a value of 46.25.